The de facto procedures of student action and the rights to defense and due process of the university teaching staff: an analysis of the "right" to veto by students - Ulrich Astaiza, William Eugene; Campo Baena, Ingrid Jimena (DIXI, 2019)
Introduction: In the relations between university students, both in the public and private spheres, there are often nonconformities, either methodological or personal, that show the weakness of university education systems regarding the handling of conflicts and their timely resolution. This has created de facto procedures like the "veto that becomes a de facto path."Objective: to determine, through jurisprudence and the law, a legal disciplinary procedure that complies with the fundamental rights that govern the differences between the student and the teacher, and vice versa.Methodology: through an analysis of the jurisprudence of the Constitutional Court and the application of procedures determined in Colombian law, a proposal is made for a viable procedure to solve the differences that arise between students and teachers.Outcome: a form of judgment is proposed that allows, in accordance with existing living arrangements or disciplinary regulations, to exercise the defense, contradiction, presentation and practice of evidence, as well as the right to a verdict in conditions of impartiality and with the option of presenting the resources that are needed.Conclusions: teachers and university students are encouraged to propose such situations in their internal meetings, so that discussion is generated in order to reach a consensus that allows the visibility of this problem and, of course, legal to prevent such situations from being perpetuated as a de facto mechanism of action.
Keywords: due process; right to defense; pupil; university; via de facto